Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - Review Exercises: Chapter 7 - Page 497: 35



Work Step by Step

$(g-h)(-2)=g(-2)-h(-2)$ $g(-2)=3(-2)-6=-12$ $h(4)=(-2)^{2}+1=5$ $(g-h)(-2)=-17$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.